Phytoremediation Potential of Four Native Plants in Soils Contaminated with Lead in a Mining Area - Nan Lu (MDPI AG, 2021)
Metal pollution in soils is an issue of global concern, and lead (Pb) pollution is considered to be the most serious type. The arid and semi-arid areas of Northwest China are rich in Pb ore resources. In this study, four native crops [wormwood (Artemisia capillaris), dandelion (Taraxacum mongolicum), alfalfa (Medicago sativa), and plantain (Plantago asiatica L.)] that grow naturally around tailings slag in a mining area in Northwest China were selected to screen their ecological restoration impacts on Pb-contaminated soil. In pot experiments, four different metal lead pollution gradients (0, 2, 3, and 5‰ w/w) were set, and crop growth indexes such as plant height, root length, and biomass, together with the changes of soil Pb content in different tissues and organs before and after planting were analyzed. The results showed the difference in the amount of accumulated Pb in relation to the level of Pb content in the soil. It was found that wormwood and plantain have great potential as remediation plants for soil metal lead pollution in the arid and semi-arid lead bearing mining areas of Northwest China.